2013
DOI: 10.1158/0008-5472.can-12-3322
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Activation of CD56+ Immune Cells That Eradicate Neuroblastoma

Abstract: Despite the use of intensive contemporary multimodal therapy, the overall survival of patients with high-risk neuroblastoma is still less than 50%. Therefore, immunotherapy without cross-resistance and overlapping toxicity has been proposed. In this study, we report the development of a novel strategy to specifically activate and expand human CD56

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…NCAM1, also known as CD56 is part of the immunoglobulin superfamily and is expressed on the surface of neural cells [23] and certain cells of the immune system [24]. NCAM1 is classically known as a cell surface molecule and cell adhesion in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM1, also known as CD56 is part of the immunoglobulin superfamily and is expressed on the surface of neural cells [23] and certain cells of the immune system [24]. NCAM1 is classically known as a cell surface molecule and cell adhesion in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical studies have shown that NK cell infusion has good efficacy as an immunotherapy for NB [26]. However, NK cells express a complicated range of receptors, such as inhibitory and activating receptors, and their binding to different ligands may affect the efficacy of immunotherapy in NB [27].…”
Section: Discussionmentioning
confidence: 99%
“…Starting with PBMC enriched for CD56 cells together with the corresponding non-CD56 PBMC in a 1:1 mixture favors a 89-fold NK cell expansion with a final product consisting of 92% NK cells after 21 days (69). Alternatively, adding irradiated autologous PBMC to the culture is a strategy to benefit from these “feeder cells” for NK cell activation and expansion but to avoid their coexpansion (Table 3).…”
Section: Autologous Accessory Cells and Autologous Feeder Cells For Nmentioning
confidence: 99%
“…A first feasibility study of automated NK cell cultivation with a stirred bioreactor was already published in 1996, showing advantages of the bioreactor culture over manually handled controls (159). More recently, different investigators report automated NK cell expansion procedures with a rocking motion bioreactor (67, 69, 156, 160), yielding 2–10 × 10 9 NK cells under GMP-compliant conditions. However, the latter system still needs preceding manual cultivation, because relatively high cell numbers are required as inoculum for the automated culture (67, 69, 156, 160).…”
Section: Technical Aspects Of Nk Cell Expansionmentioning
confidence: 99%
See 1 more Smart Citation